Implementation of the Picture and Picture Method to Model in Improve Early Childhood Speaking Skills - Prima, Elizabeth; Putu Indah Lestari; Ni Komang Theda Febrina Subagia (Jurnal Pedagogi dan Pembelajaran, 2025)
Children's language development is strongly shaped by environmental stimulation from parents, teachers, and caregivers. Speaking ability is key for communication and social adaptation, yet many children still struggle to form simple sentences and express ideas verbally. The study aims to analyze the effectiveness of the Picture and Picture learning model in improving the speaking skills of early childhood children. This study used a quasi-experimental approach with a pre-test and post-test research design in the control group and experimental group. The research subjects were kindergarten children with a sample size of 60 children selected through random sampling technique. The experimental group consisted of 30 children who received learning using the Picture and Picture model, while the control group consisted of 30 children who received conventional learning. Data collection was carried out using an early childhood speaking ability assessment rubric before and after intervention, which was analysed using the One-Way Anova statistical test. The results showed that there was a significant difference between the experimental group and the control group in improving speaking ability. Data analysis shows that the treatment using Picture and Picture model gives a greater effect on improving speaking ability compared to conventional methods. The implications of this study indicate that the use of innovative image media in learning can be an effective strategy in improving early childhood speaking skills and providing a more interesting and interactive learning experience.